Analysis of soil microbiome indicators in processes of soil formation, organic matter transformation and processes involved with fine regulation of vegetative processes - E. E. Andronov; E. A. Ivanova; E. V. Pershina; O. V. Orlova; Yu. V. Kruglov; A. A. Belimov; I. A. Tikhonovich (Бюллетень Почвенного института им. В.В. Докучаева, 2015)
At the current stage of soil microbiology development the study of the entire complex of microorganisms inhabiting the soil became possible, which helps finding the optimal combination of factors resulting in the formation of soil fertility as well as the development of stable and stress resistant phytocenosis. Soil metagenome is the largest genetic depository for all purposes, from the soil formation processes - transformation of barren rock into a substrate for plant growth and development, to the temporary adaptations in the short-term interests of the plant. The investigation of genetic potential of soil metagenome and its mobilization are the main goals of this project. Such studies should be comprehensive and solve actual issues: 1) the study of the mechanisms of soil-forming processes and the analysis of the evolution of metagenomes due to the special features of pedogenesis; 2) investigation of microbiome participation in organic residues decomposition and efficient transformation of soil organic matter; 3) screening of the associative plant-protective and growth promoting microorganisms. The object for the analysis of microbiome evolutionary potential in the process of soil formation may be the technogenic dumps resulting from mining operations, which are chronosequences of soils of different ages. Samples of paleosols are also of particular interest in the evolutionary aspect of the analysis of the soil metagenome. The project is expected to reveal a group of soil microorganisms, which take the most active part in the formation of soil fertility and effectively implement growth-stimulating and protective functions for the plant. The data may be of value for both fundamental science and serve as a base for the design of environmentally friendly high-productive phytocenoses based on the use of the adaptive potential of soil microbiota.